2012
DOI: 10.5056/jnm.2012.18.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Deglutitive Inhibition, Latency Between Swallow and Esophageal Contractions and Primary Esophageal Motor Disorders

Abstract: Swallowing induces an inhibitory wave that is followed by a contractile wave along the esophageal body. Deglutitive inhibition in the skeletal muscle of the esophagus is controlled in the brain stem whilst in the smooth muscle, an intrinsic peripheral control mechanism is critical. The latency between swallow and contractions is determined by the pattern of activation of the inhibitory and excitatory vagal pathways, the regional gradients of inhibitory and excitatory myenteric nerves, and the intrinsic propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…Computational modeling of colonic wall contraction and flow dynamics has recently shown that perturbation of descending inhibition can lead to less efficient bolus transit and increased intraluminal pressures, 15 a finding that is analogous to the observation of increased intrabolus pressures in the current study. We note that impaired descending inhibition has been previously characterized in dysphagia patients 16 and it has been recently shown that multiple rapid swallowing, a test designed to uncover deficiencies in descending inhibition of the esophagus, has been found to be a predictor of post fundoplication dysphagia 17 . Whereas multiple rapid swallowing may provide an indirect marker of inhibitory failure, AIM analysis, through measurement of elevated pressures within the bolus, may provide more direct markers of impaired descending inhibition.…”
Section: Discussionmentioning
confidence: 86%
“…Computational modeling of colonic wall contraction and flow dynamics has recently shown that perturbation of descending inhibition can lead to less efficient bolus transit and increased intraluminal pressures, 15 a finding that is analogous to the observation of increased intrabolus pressures in the current study. We note that impaired descending inhibition has been previously characterized in dysphagia patients 16 and it has been recently shown that multiple rapid swallowing, a test designed to uncover deficiencies in descending inhibition of the esophagus, has been found to be a predictor of post fundoplication dysphagia 17 . Whereas multiple rapid swallowing may provide an indirect marker of inhibitory failure, AIM analysis, through measurement of elevated pressures within the bolus, may provide more direct markers of impaired descending inhibition.…”
Section: Discussionmentioning
confidence: 86%
“…We believe that MII measurements can detect changes in the esophageal CSA fairly accurately and may provide useful information on the inhibitory phase of peristaltic reflex. Studies show that patients with spastic motor disorder of the esophagus have impaired inhibitory innervation as measured by impaired relaxation of the artificial high-pressure zone (15, 16). However, those studies have only been performed in a limited number of patients as they are not practical.…”
Section: Discussionmentioning
confidence: 99%
“…Two broad categories of abnormalities can be seen with multiple rapid swallows: (i) incomplete inhibition wherein contraction fragments are seen during the expected phase of inhibition and (ii) suboptimal contraction wherein there is failure of augmentation of contraction in the sequence following the last swallow of the series (Figure 1). In extreme settings, contraction may fail altogether (2,3). We have previously reported that an abnormal MRS response using these crude measures can be associated with dysphagia after antireflux surgery (2).…”
Section: Introductionmentioning
confidence: 99%